The Influence of Reward and Communication to Cohesion Team of Tuberculosis Prevention Team in Community Health Centers (Indian Journal of Public Health Research & Development, 2020)
Tuberculosis is an infectious disease caused by the tuberculosis virus, Mycobacterium tuberculosis.Indonesia is the third country after India and China that has 420.994 tuberculosis cases. East Java wasranked in the second among other provinces in Indonesia with more than 20.000 newly cases. Surabayahas the highest number of tuberculosis cases in East Java with the success rate of less than 90%. The keyrole of a community health center is to support the program of tuberculosis prevention but the organizationfrequently did not achieve the goal of health program. The study was an observational analytic on the teamof tuberculosis prevention in Surabaya’s community health centers. The sample was taken using stratifiedrandom sampling and chose 43 teams of tuberculosis prevention with simple random sampling. Total ofparticipants was 318 people consisted of a doctors, nurses, and health analysts. The statistical analysis wasa linear regression test. The findings showed reward influenced significantly toward team cohesion, whilecommunication variable did not influence to team cohesion. The research concluded there was an influenceof intrinsic reward toward cohesion in a team. Team cohesion is one of team process enabling to supportteam performance to achieve program target of tuberculosis prevention so it suggested paying attention totheir staff particularly intrinsic reward by the management.
Keywords: Communication, intrinsic reward, team cohesion, tuberculosis.